Derechos vulnerados y desafíos legales enfrentados por servidores de la Policía Nacional: enfoque en la extralimitación en actos de servicio periodo 2020 - 2023 - Peña Yaguachi, Priscila Elizabeth (2024)
The progressive use of force is a doctrine that establishes that force should be used in a proportional, gradual, and adequate manner to the specific situation, minimizing damages and injuries. In Ecuador, this concept is recognized both by law and by a specific regulation on the progressive use of force. In this context, there are rulings issued at the international level by the Inter-America Court of Human Rights, and at the national level, there are different judicial instances that ensure the application of law and the protection of rights in accordance with the Constitution of the Republic of Ecuador and Ecuadorian laws. The general objective of this study was to analyze the violated rights, and the legal challenges faced by the servants of the National Police of Ecuador with a particular focus on the excesses in acts of service in the cases of Wilson Santiago Olmedo Gordillo and Aroca Palma and others Vs Ecuador, who have been sentenced during the 2020-2023 period. The methodology used was a qualitative approach with the application of a descriptive and exploratory research through the analysis of the study of two specific cases, Wilson Santiago Gordillo y Aroca Palma among others Vs. Ecuador, from which it was obtained relevant data from the analysis of the judgments in the case. Regarding the international level, the Inter-American Court declared that Ecuador is internationally responsible for the violation of articles 4.1, 5.1, 7.1, 7.2, 7.4, 7.5, 8.1 y 25.1 of the American Convention on Human Rights; meanwhile, the Specialized Criminal, Military Criminal, Police Criminal and Traffic Chamber of the Provincial Court of Justice of Chimborazo declared Santiago Olmedo guilty of excessive use of force and sentenced him to 13 years in prison. Furthermore, he was fined and ordered to pay reparations to the victim’s families. Finally, these cases describe the importance of reviewing and improving police action protocols as well as ensuring equitable justice that considers all circumstances involved in incidents of this type.